(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Purpose of Study: This study exclusively focused on private HEIs due to the growing trend of Malaysian students opting for private HEI to further their study. The purpose of this research is to determine the direct relationship between tuition fees and students’ decision-making to enrol at private HEI; and to determine the indirect relationship where financial aid moderates the relationship between tuition fees and the students’ decision-making to enrol at private HEI. Methodology: The underpinning theory applied in this study was Theory of Planned Behavior (TPB) applied for tuition fees. Five hundred (500) questionnaires distributed at selected private HEI around Kuala Lumpur and Selangor. The unit of analysis for this study was the first-year undergraduate students (in their first academic semester in 2018) at 23 selected private HEIs across Kuala Lumpur and Selangor. Data were analyzed using variance-based structural equation modelling (VB-SEM) technique. Results: The analysis outcome of the focal study had expounded a positive significance relationship between TF and DM. While, the result of moderation assessment had confirmed that the FA played a significant moderation role on relationship path between TF and DM indicated by t and p values that surpassed the minimum threshold. Thus, analysis on structural model had further verified that hypotheses h1 and hypotheses h1a of focal study were accepted. Implications: A positive significance relationship between TF and DM indicated by path coefficient of  0.387; t-value of 7.217 and p-value of 0.000. The was a moderation effect of FA (Financial Aid) on the relationship between TF and DM explained by path coefficient  = -0.098 and furthered validated its significance by bootstrapping routine of two-tailed test with p-value of 0.011 and t-value of 2. 627.